Analysis into the selection of a ballast water treatment system - Šateikienė, Diana; Janutėnienė, Jolanta; Bogdevičius, Marijonas; Mickevičienė, Rima (Transport, 2015)
Today, it is very important to select and install the optimal equipment for the treatment of ballast water in existing ships. Increasing cargo volumes demand for a greater number of ships for transportation and expanded navigation geography as well as result in increased amount of discharged ballast water. Consequently, sea water pollution is increasing and invasive microorganisms appear that the existing flora and fauna are unaccustomed to. In order to protect territorial waters from these invasive species, International Maritime Organization (IMO) requirements have been implemented that regulate the quality parameters of discharged ballast water from ships. This problem has become particularly relevant for operational ships, in which ballast water treatment equipment and technical solutions had not been anticipated in the design stage. This article provides a comparative analysis of the treatment equipment of ballast water and the related technical parameters, in order to distinguish the most important equipment criteria. A Carrier, according to its technical characteristics, was analysed together with the water treatment method for operated bulk. An expert evaluation for the characteristics of the technical equipment was established.